Religion as a value during the pandemic. Sociological analysis - Sławomir Henryk Zaręba (Journal of Modern Science, 2021)
Objectives This work presents the results of sociological research carried out by the staff of the Polish Research Laboratory for the Assessment of Attitudes and Values. Its title is “University Students on Family and Religion 2020” . Within the multi-stranded research applications, one thematic segment pertained to the religious attitudes of university students during the pandemic. From the perspective of religious experience, a component of the sociological model in researching religiosity, this work reveals the attitude of the respondents to religion as a value in general, but also a value which makes sense of human life. Here, we find an answer to the question of bonding with God without the Church as a religious institution, as well as the perception of the pandemic whether as a biological phenomenon or as a punishment for sins.